An assessment of own revenue management for financial sustainability of the Eastern Cape municipalities - Majikijela, Vuyolwethu (Rhodes University, Faculty of Commerce, Rhodes Business School, 2018)
The purpose of the research is to assess the financial viability of municipalities in the Eastern Cape. Municipalities that are not financially viable and sustainable will always struggle to deliver basic services to communities. Without sound financial management systems, municipalities will be forced to discontinue their operations. Municipalities, particularly small and rural ones, are not self-sufficient thus cost benefit theory emphasises that municipality must adopt cost recovery revenue management. The application of cost recovery revenue management requires that municipalities take into account internal and external revenue management challenges that will be factored on user charges. Cost recovery also requires governance to lead the process through capacitation, transparency and communication with all stakeholders. This research highlights that municipalities in the province have not matured to a level wherein they are able to adopt cost recovery revenue management because of prevalent external revenue management challenges caused by high unemployment rate in the province and the slow economic growth. Municipalities in the province are thus financially unsustainable. This research therefore proposes that a phase in approach to cost recovery should be adopted in line with the changes in unemployment and economic growth. Increased transparency and consultation with intergovernmental relations should also be promoted to enable financial sustainability of municipalities in the province.
Keywords: Revenue management; Municipal government -- South Africa -- Eastern Cape; Municipal government -- South Africa -- Eastern Cape -- Finance; Municipal government -- South Africa -- Eastern Cape -- Cost effectiveness; Municipal services -- Finance